Propagation Analysis Using Discrete Mixed Fourier Transform-Based Parabolic Equation Method for Long Range Radar Detection Error Correction - Heo, Jun; Yang, Junmo; Kim, Jongmann; Na, Dong Yeop; Park, Yong Bae (IEEE Access, 2023)
This paper proposes a novel method to predict the radar detection errors in a complex environment by considering slant range and angular error. This method involves analysis of the electromagnetic wave propagation path loss in troposphere using discrete mixed Fourier transform based split-step parabolic equation. For analysis, modeling of the terrain profile using a digital elevation model and estimating the refractive index by interpolating upper-air observations is conducted. The direction of refracted antenna's main beam is predicted using the path loss, and by comparing it with the antenna boresight, the radar errors are computed according to the received timing of the radar echo. To apply the proposed method to real scenarios, the atmospheric environment within the analysis area is modeled using meteorological data collected on a specific day. By applying the proposed method to an arbitrary date and location, the radar errors in a long-range propagation environment where refraction occurs are analyzed.
Keywords: Angular errors; Atmospheric modeling; Detection error; Mixed fourier transforms; Parabolic equation method; Path loss; Radar detection; Radars antennas; Range error; Slant range error; Angular error; parabolic equation method; radar detection; slant range error